Ember eternal - Neill, Chloe (Souls burn brightest, 2025)
"A new romantasy, following a thief whose dramatic encounter with an assassin and a crown bodyguard (who happens to be a royal in disguise) launches her into a world of swirling palace intrigue, from New York Times bestselling author Chloe Neill. Fox is a thief with morals-she steals from those who can afford it and only a little at that. She has no choice. Fox and her closest companion are indentured servants to a wealthy noble in the stronghold. Unable to pay off their familial debts with the work they're given, they steal in the hopes of one day being free-truly free. While searching for an easy mark in town, Fox helps a royal bodyguard fend off a would-be assassin's attack on a prince's life. But what started off as protecting the prince out of good conscience has now unwittingly embroiled this thief in a vast world of politics, high stakes, and romance. And though Fox longs to be rid of her debts, she must decide if love is its own kind of cage"-- Provided by publisher.